GENERAL THEORETICAL BASIS OF CREATING A DATABASE OF DIALECTS OF THE FERGANA REGION (Scientific journal of the Fergana State University, 2026)
This article examines the general theoretical foundations for creating a database of Fergana region dialects. It analyzes the ethnogenesis of the Uzbek people and its influence on linguistic diversity. The significance of dialectology as a science, and the essence of the concepts of sheva (dialect), lahja (sub-dialect), and dialect are thoroughly explored. Furthermore, the contributions of scholars such as Mahmud Kashgari, Alisher Navoi, and Zahiriddin Muhammad Babur to Uzbek dialectology, as well as significant research conducted in this field in the 20th century, are investigated. The article justifies the relevance of digitizing dialects and creating electronic corpora, demonstrating the linguistic, practical, and social advantages of this process. In particular, it highlights the value of a dialectal corpus as a source for phonetic, lexical, morphological, and syntactic analyses, its role in developing speech synthesizers, and its convenience for regional users and researchers. The article concludes by emphasizing the necessity of creating a dialectal corpus in Uzbek linguistics and its future scientific and practical potential.